Three new species of Melolontha Fabricius from southern China (Coleoptera: Scarabaeidae: Melolonthinae) - Wang, Fa-Lei (Zootaxa, 2024)
Three new species of the M. aeneicollis species group of the genus Melolontha Fabricius, 1775 are described from southern China: M. jianbini sp. nov. from Gutian County, Fujian province; M. tianlongi sp. nov. from Suichuan County, Jiangxi province; and M. xui sp. nov. from Yangshan County, Guangdong province. A key to the species of the M. aeneicollis species group is also provided.